1991
DOI: 10.1093/ajcn/53.6.1460
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and household risk factors for xerophthalmia in Aceh, Indonesia: a case-control study

Abstract: Risk factors for xerophthalmia were assessed in 466 subjects [38% with night blindness (XN), 60% with Bitot's spots (X1B), 2% with corneal xerophthalmia (X2 or X3)] under age 6 y and their village-age-sex-matched control subjects during a community trial. Socioeconomic status and hygiene standards were lowest for households of xerophthalmic children and highest for nonstudy households in the trial population, with values for control households lying in between (P less than 0.001 by linear trend). Risk of xerop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 24 publications
1
34
1
2
Order By: Relevance
“…Another study in Nepal by Christian et al (1996) also showed that XN pregnant women were less likely to have consumed milk, mangoes and DGLV than that of matched controls. A study in Aceh, Indonesia used logistic regression analysis to examine the relationship of various factors with xerophthalmia and reported that the consumption of DGLV, yellow fruits and eggs was inversely related to the risk of xerophthalmia (Mele et al, 1991). Multiple regression analysis of our data reveals that the frequency of intake of DGLV is signi®cantly independently related to serum vitamin A level.…”
Section: Discussionmentioning
confidence: 68%
“…Another study in Nepal by Christian et al (1996) also showed that XN pregnant women were less likely to have consumed milk, mangoes and DGLV than that of matched controls. A study in Aceh, Indonesia used logistic regression analysis to examine the relationship of various factors with xerophthalmia and reported that the consumption of DGLV, yellow fruits and eggs was inversely related to the risk of xerophthalmia (Mele et al, 1991). Multiple regression analysis of our data reveals that the frequency of intake of DGLV is signi®cantly independently related to serum vitamin A level.…”
Section: Discussionmentioning
confidence: 68%
“…The relation between dietary practice and prevalence of xerophthalmia is well documented (Hussain et al 1993;Tarwotjo et al 1982;Sole et al 1987;Fawzi et al 1993;Mele et al 1991;Cohen et al 1985b). Studies conducted by Tarwotjo et al (1982), Sole et al (1987) and Fawzi et al (1993) suggested that increased consumption with provitamin A-rich foods is likely to reduce the occurrence of nutritional blindness.…”
Section: Discussionmentioning
confidence: 96%
“…[72][73][74][75][76][77] Night blindness and/or con-junctival signs of vitamin A deficiency have been associated more commonly with stunting. [74][75][76] However, most of these studies were cross sectional and did not adequately control for confounding variables that are commonly associated with vitamin A deficiency (e.g.…”
Section: Observational Studiesmentioning
confidence: 99%